2015
DOI: 10.1155/2015/165412
|View full text |Cite
|
Sign up to set email alerts
|

Content and Bioaccumulation of Nine Mineral Elements in Ten Mushroom Species of the GenusBoletus

Abstract: Concentrations and bioconcentration potential of nine elements (Ca, Cu, Fe, K, Mg, Mn, Na, P, and Zn) in ten species of wild edible Boletus and the corresponding underlying soils were analyzed. The analyses were performed using inductively coupled plasma atomic emission spectrophotometer. Boletus showed relative abundant contents of P, K, Fe, Mg, Ca, and Na and less of Zn, Cu, and Mn. Caps compared to stalks were enriched in P, K, Cu, Mg, and Zn, while stalks were enriched in Mn. The elements such as P and K w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 32 publications
2
15
0
Order By: Relevance
“…On the other hand, the example of the highly diverse F. velutipes and A. mellea (both belong to Physalacriaceae family) indicates that it is not only family but also tree species that may influence the content of elements in fruit bodies. Similarities or differences in element accumulation between some mushroom species of the same family have been described in numerous papers (Wang et al 2015). As in our paper, Chemghom et al (2010) reported the highest content of Ca and a high content of Mn in P. igniarius, Flammulina velutipes grown on Acer negundo, and A. mellea on Populus alba L.; what is especially important is that Acer is generally characterized by more effective phytoextraction of elements from soil than Populus (Tangahu et al 2011;Mleczek et al 2017a).…”
Section: Discussionsupporting
confidence: 84%
“…On the other hand, the example of the highly diverse F. velutipes and A. mellea (both belong to Physalacriaceae family) indicates that it is not only family but also tree species that may influence the content of elements in fruit bodies. Similarities or differences in element accumulation between some mushroom species of the same family have been described in numerous papers (Wang et al 2015). As in our paper, Chemghom et al (2010) reported the highest content of Ca and a high content of Mn in P. igniarius, Flammulina velutipes grown on Acer negundo, and A. mellea on Populus alba L.; what is especially important is that Acer is generally characterized by more effective phytoextraction of elements from soil than Populus (Tangahu et al 2011;Mleczek et al 2017a).…”
Section: Discussionsupporting
confidence: 84%
“…Magnesium was not correlated with these elements, but it had rho values between 0.41 and 0.53 with transitional metals such as Ag, Cd, Cu, and Fe. An interesting finding was the significant inverse correlation of sulphur with Ca, Ba, Sr, and Mn, and stronger positive correlation with Ag, Cd, Zn, and P. We also found significant correlations between other pairs of elements such as Fe-Mn, Fe-Cr, Fe-Na, K-Na, K-Al, Fe-Al, Cd-Zn, Cd-Ag, and Cu-Mg. Other studies on mushrooms found the same correlations between elements [4,29]. In order to assess the contribution of some heavy metals to the health risk of mushroom consumption, we calculated the hazard quotients.…”
Section: Resultsmentioning
confidence: 76%
“…Mushrooms are an important source of proteins, dietary fibres, and vitamins (B, C, D, E) containing low levels of sugar and fats. They can assimilate large amounts of water and minerals such as phosphorus, iron, potassium, cadmium, magnesium, copper, and zinc, due to the large area of mycelium overgrowing the surface layer of soil [ 9 ]. This mycelia network is ideally suited to penetrate and access soil pore spaces and an extensive surface area of fungal hyphae and physiology enable for many species on effective absorption and bioconcentration of various metallic elements, metalloids, and nonmetals [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…This mycelia network is ideally suited to penetrate and access soil pore spaces and an extensive surface area of fungal hyphae and physiology enable for many species on effective absorption and bioconcentration of various metallic elements, metalloids, and nonmetals [ 10 ]. Bioconcentration factor (BCF), the ratio of the element content in fruiting body to the content in underlying substrate, can express the ability of fungi to accumulate elements from substrate, and this capacity of the mushroom is affected by fungal lifestyle, age of fruiting body, specific species and element, and environment such as pH, organic matter, and pollution [ 9 ]. Moreover, the symbiotic relationships that some mushrooms species, namely, A. ponderosa, can establish with some plants of their habitats allowing the accumulation of high concentrations of some metals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation